Cannabis withdrawal induced brief psychotic disorder: a case study during the national lockdown secondary to the COVID-19 pandemic. Issue 4 (1st October 2021) - Marín, Julen; Pérez de Mendiola, Xabier; Fernández, Sergio; Chart, Juan Pablo
Abstract: Background: Cannabis Withdrawal Syndrome (CWS) is a key feature of Cannabis Use Disorder (CUD). The CWS causes significant distress and disability. While the relationship between CUD and psychosis has been extensively studied, the potential connection between CWS and psychosis has not received as much attention. Case presentation: The CARE guideline's methodology is followed in the presentation of this case report. During the national lockdown decreed by the Spanish government for the containment of the CoronaVirus Disease 19 (COVID-19) pandemic, a 29-year-old man suffers a CWS and a subsequent psychotic episode. He is admitted to a psychiatric unit, obtaining a rapid and complete response to treatment. Discussion: Clinical and pathophysiological data that support the hypothesis of CWS-induced psychosis are discussed. Due to the increasing use of cannabis worldwide, we believe that more research is needed on the mental disturbances associated with CUD, including CWS and psychosis. On the other hand, the confinement and social distancing measures adopted in the face of the current COVID-19 pandemic could have restricted the availability and consumption of certain drugs, precipitating the emergence of withdrawal syndromes such as CWS.